‘Are they out to get us?’ Power and the ‘recognition’ of the subject through a ‘lean’ work regime - Mackenzie, Ewan; McGovern, Tom; Small, Adrian; Hicks, Chris; Scurry, Tracy (Organization studies, 2021)
Critical studies of ‘lean’ work regimes have tended to focus on the factory shop floor or public and healthcare sectors, despite its recent revival and wider deployment in neoliberal service economies. This paper investigates the politics of the workplace in a United Kingdom automotive dealership group subject to an intervention inspired by lean methods. We develop Foucauldian studies of governmentality by addressing lean as a technology of power deployed to act on the conduct of workers, examining how they debunk, distance themselves from and enact its imperatives. Our findings support critiques of lean work regimes that raise concerns about work intensification and poor worker health. Discourses of professional autonomy allow workers to distance themselves from lean prescriptions, yet they are reaffirmed in their actions. More significantly, we illustrate the exercise of a more encompassing form of power, showing how lean harnesses the inherently exploitable desire for recognition among hitherto marginalised workers, and its role as a form of ‘human capital’. The paper contributes to critical studies of lean by illustrating its subtle, deleterious and persistent effects within the analytical frame of neoliberal governmentality. We also demonstrate how studies of governmentality can be advanced through the analysis of contested social relations on the ground, highlighting the ethico-political potential of Foucauldian work.